’˜STUDENT LADY HEALTH VISITORS’: THEIR STRESS PROFILE AND WILLINGNESS TO PRACTICE - Siddiqui, Saad; Shah, Noreen; Ayub, Romana; Khan, Naseer (Journal of Ayub Medical College Abbottabad, 2012)
Background: Lack of Reproductive health facilities including high maternal and neonatal mortality is a major problem of our region. Skilled healthcare providers like Lady Health Visitors can play a significant role in improving parameters of reproductive healthcare. The objectives of this study were to assess stress profiles in student lady health visitors and their willingness to practice in future. Methods: Cross sectional survey conducted at two public health schools in District Peshawar with student Lady Health Visitors as study participants. Results: Majority (64.4%) of respondents were satisfied with their choice of career, 78% thought they had adequate knowledge to practice independently, 47.7% thought that their life in this profession will be stressful. Most of them were facing financial difficulties during their course, 84.8% enjoyed support of their family in choice of career, 50-82% reported psychosomatic problems arising as result of stress in their lives. Conclusion: Most of the respondents were happy with their choice of profession and were willing to practice in future. High prevalence of stress in lives of respondents warrants counselling services by institutions. Keywords: Lady Health Visitors, Stress, Health professionals, Public health, Women, Cultural restrains